Prevalence of Acrobacter spp on chicken meat at retail markets and in farm chickens in Selangor, Malaysia. - Amare, L.B.; Abdul Aziz, Saleha; Zakaria, Zunita; Abu, Jalila; Hassan, Latiffah (Elsevier, 2011)
The occurrence of Arcobacter was determined in chicken meat parts (thighs, wings, breasts) purchased from various wet markets (fresh warm meat) and supermarkets (chilled meat) in Selangor, Malaysia. Forty eight of the 123 (39%) of chicken meat parts was Arcobacter-positive with Arcobacter butzleri as the only species isolated. The fresh warm meat (41%) showed higher occurrence of arcobacters than those chilled (37%), however the difference was not statistically significant (χ2 = 0.2; p = 0.655). A farm-level study was also conducted in broiler chickens from six farms but the bacteria were not detected in any of the 210 cloacal swabs collected. Thus, the presence of arcobacters on chicken meat retailed in markets may render such meat a significant public health risk for humans.